Antioxidative Metabolism in the Seedlings of Pigeonpea in Response to Lead and Cadmium Stress - B. Priyadarshini, B. Sujatha* and (Journal of Phytology, 2011)
Effects of Pb and Cd stress on antioxidative systems were studied in pigeonpea (Cajanus cajan (L.) Millspaugh) cultivars T21 and LRG30. The seeds were grown under different concentrations of Pb and Cd for 8-days and activities of enzymes including superoxide dismutase, peroxidase, catalase, glutathione reductase, malate dehydrogenase were assayed. In addition, quantitative estimations of ascorbic acid and glutathione were also carried out in control and Pb and Cd treatments of pigeonpea seedlings. The activities of antioxidative enzymes showed a marked increase in response to heavy metal stress. However the ascorbic acid and glutathione content were decreased by increasing heavy metal concentrations. This study revealed that varietal differences play an important role in the plant response to heavy metals. Key words: Antioxidants, cadmium, heavy metal stress, lead, pigeonpea. <span style="font-weight: normal; font-size: 7pt; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-ansi-language: EN-SG; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no;" lang="EN-SG">B. Sujatha and B. Priyadarshini. Antioxidative Metabolism in the Seedlings of Pigeonpea in Response to Lead and Cadmium Stress J Phytol 3/5 (2011) 41-50.